PERENCANAAN USAHATANI LAHAN KERING DENGAN MEMANFAATKAN TANAMAN KELOR ( Moringa Oleifera ) SEBAGAI TANAMAN TEPI DAN LORONG UNTUK MENINGKATKAN PENDAPATAN PETANI - Fawaid, Ach; agridevina, Isdiantoni; Ekawati, Ida (Berkala Ilmiah AGRIDEVINA, 2016)
Characteristics of agricultural land in the village Talangoform of dry land, with water availability is limited, so thatthe land can not be planted throughout the year, and plantsthatcan be cultivated is limited. Mixed cropping is thedominant of cropping system. The productivity is low, so itneed plant arrangement in the cropping system bycombining annual crops (food crops) with perennial crops(ei. Moringa). The principle of this combination to meet theneeds of farmers (food, feed and cash income), so that theMoringa is also used as the climbing pole of chilli plantsherbs. This study, aimed to estimate the production of anytype of cultivated plants and the revenue generated fromeach model cropping systems are planned, as well as thecontribution of the moringa plants and herbs chili on farmincome. The descriptive research conducted by identifying,evaluating, designing, and estimeted of the cost,production, revenue and R/C ratio of the model based on aliterature review and field observation. Total production for2 years of the edge cropping system model and alleycropping reached 8671.12 kg and 8855.16 kg respectively.Farm income per hectare reach Rp 39.014.800 and Rp23,654,200,-respectively. The contributions of Moringa andchilli herbs on farm incomes of edge cropping systems4.66% and 11.99% respectively. Meanwhile, alley cropping19.82% and 50.98% for Moringa and respectively.Keywords: dry land, cropping system, the needs offarmers.